Teaching and Learning Problems of the Orang Asli Education: Students’ Perspective - Abdullah, Ramle; Wan Mamat, Wan Hasmah; Wan Ismail, Wan Ahmad Amir Zal; Ibrahim, Asmawi Mohamad (2013)
The standard of education among the Orang Asli people as an indigenous ethnic in Malaysia is still at a low level. The majority of the Orang Asli people receive formal education only at the primary level. However, there is a significant trend where the majority of students who completed their primary education will drop out from secondary school. Hence, only two percent have been successful in advancing their higher education in tertiary institutions. Such problems are commonly associated with several factors, including students’ attitudes, awareness among parents about education, local culture, school leadership, school environment, and problems related to the teaching and learning process. For better understanding of this problem, a specific research was carried out to study the Orang Asli students in Kelantan. The research focused on students’ perspectives based on the questions: What are the teaching and learning methods often used by teachers? What are the common problems related to the teaching and learning of the Orang Asli students? What are students' perceptions toward the teaching and learning methods used? The research using qualitative methods involved four Orang Asli villages in the state of Kelantan. Data were collected through interviews, focus group discussion and observation. The respondents consisted of children and young adults. Results showed that teaching pedagogy are generally stereotyped and unable to stimulate students’ interest. The common problem in the teaching and learning is related to the attitude and commitment of teachers in the teaching and learning process. The implications of the problems and teachers' attitudes are significantly associated with degrading interest among students on education, issues of attendance and students’ academic performance.